Publicness Pada Sekolah Kopi RAISA Dalam Pengembangan Kopi Rakyat di Kawasan Ijen Geopark Kabupaten Bondowoso - Anindya Safira (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Jember, 2026)
This study aims to describe and analyze the role of the RAISA Coffee School in the development of smallholder coffee in Sumberwringin District, Bondowoso Regency. The background of this research is based on the limited role of formal government institutions in meeting the real needs of smallholder coffee farmers, thus encouraging the emergence of the RAISA Coffee School as a community-based nonformal learning institution. This study used a descriptive qualitative approach. Data collection techniques included observation, in-depth interviews, and documentation. Research informants included the RAISA Coffee School management, administrators and technical assistants, smallholder coffee farmers, and local government representatives. Data analysis was conducted interactively through the stages of data reduction, data presentation, and conclusion drawing. The results indicate that the RAISA Coffee School carries out functions that intersect with the public interest despite not being a government institution or formal public organization. Analysis using Bozeman's (2011) publicness perspective indicates that the public character of the RAISA Coffee School is reflected through the normative publicness dimension, which includes open access to learning, meaningful farmer participation, transparency based on social relations, and equitable distribution of benefits. The most prominent publicness values are respect for farmer dignity and social sustainability in the smallholder coffee development process.
Reuploud file repository 25 mei 2026_Firli_Tata
Keywords: Publicness; RAISA Coffee School; People's Coffee; Non-formal Institutions; Public Administration